The Capital Structure Theories in World Literature - Jakubczyk, Beata; Lewandowska, Justyna (Journal of Finance and Financial Law, 2014)
In this article, will be presented the evolution of capital structure in world literature. The article shows the essence, the measurement and the importance of capital structure and capital structure theories have been presented, as well as their development over time. Cash flow used in analyses related to the verification of the capital structure.